Factors Influencing Digital Proficiency in Middle Managers within the Malaysian Public Sector - Yusfaidzira Ahmad Yusof; Hemaloshinee Vasudevan (Journal of Management Studies and Development, 2026)
The Malaysian public sector is experiencing rapid digitalization, necessitating the development of high digital proficiency among middle managers. Digital proficiency refers to the ability of an individual to consume, utilize, manage, and create digital content using digital technology. In the context of rapid digital transformation within the MPS, the primary challenge is to identify the factors that enhance digital proficiency and their effects on middle managers. The study aims to examine the relationship between digital proficiency and factors like self-efficacy, digital organizational culture, digital infrastructure, and digital training among middle managers in the Malaysian Public Service. The study utilized a non-probability convenience sampling method, involving 287 middle managers from the public sector who participated in the survey through Google Form. Data is analyzed using SPSS software for descriptive statistics, reliability, variable correlation, multiple regression, ANOVA, and multicollinearity assessment. Self-efficacy (H1: β = 0.763, t = 20.27, p < 0.001), organizational culture (H2: β = 0.089, t = 2.13, p = 0.034), digital infrastructure (H3: β = 0.082, t = 2.06, p = 0.040) is a supported factor in digital proficiency. and digital training and development (H4: β = 0.016, t = 0.40, p = 0.692) is not supported factor in digital proficiency. The MyDigital Blueprint policy is a framework that outlines the strategies for digital transformation in the Malaysian public sector.